The Influence of Social Media Use on the Political Participation of Generation Z - Sadikin, Kenanga Rahma (Actual Insight, 2025)
This research is based on the effect of the use of social media on the political participation of generation Z. The purpose of this study is to determine how the influence of the use of social media on the political participation of generation Z, as well as the impact on generation Z of the use of social media on political participation, and whether There are factors that influence the political participation of Generation Z in using social media. This study uses a survey research method with a cross-sectional design which is carried out with one answer to the questions that have been made. Methods use questionnaires. The data analysis method was carried out according to the problem formulation, with three problem formulations. The results of this study indicate that the use of social media will affect the political participation of Generation Z, in using social media there is also a positive impact on political participation of Generation Z and there are also factors in using social media that can influence Generation Z for political participation.